Capitoli autobiografici Poeti che traducono poeti dagli ermetici a Luciano Erba - Manigrasso, Leonardo (Premio Ricerca «Città di Firenze», 2013)
Leonardo Manigrasso has made use of the most up-to-date tools made available by stylistic criticism and translation studies to offer a series of intense "debates" and comparisons between the greatest poets-translators born in Italy between the 1910s and the early 1920s. The choice to cross multiple versions of the same source text allows the reader to verify the multiple ways of implicit reading and rewriting during the translation process, establishing distances, documenting unexpected dialogues, exposing the bonds between the translated work and the "creative" work of each author. The interaction between different and remarkable textual features has the goal of reconstructing a fundamental chapter in the history of twentieth century poetry, from the birth of hermetic koinè to a notion of translating as a predominantly empirical and individual process.